Morbimortality in Patients Undergone an Operation for Intestinal Occlusion in General Surgery Service - Alexander Marchena Rodríguez; Reinaldo Jiménez Prendes; Julio César Sarmiento Sánchez (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Introduction: the treatment of the intestinal obstruction depends on a premature diagnosis, a skilful and opportune- treatment handling. Objective: characterizing the behavior of the morbimortality for intestinal occlusion at Cienfuegos province, in the period from February 1st, to March 7th, 2009. Methods: a descriptive follow-up study of cases that comprised all the patients admitted and operated by intestinal occlusion. The analyzed variables were: age, sex, personal and pathological background, classification according to the American Society of Anaesthesiology, pre and trans-operative diagnostic, the surgical procedure, the location of the ward in immediate postoperative, the complementary exams, the time between the time of admission and the time of the operation, direct cause of death, the complications and the patients´ general condition on discharge. Results: the more frequent trans-operative diagnosis: bridles, intestinal tumors and hernias. The more use surgical procedures were: the lyses of bridles, the tranversostomy; the intestinal resection more practiced was the small intestine one; the more used anastomosis was the terminal term, the kelotomy and herniorrhapy. The more frequent complications were unbalance hydroelectrolític and sepsis. The principal fatal causes were: mesenteric thrombosis and disorders for hydroelectrolític unbalance, with predominance of the female sex and patients of 65 years and more. Conclusions: the advances in science, technology and health have contributed in the remission of morbidity and nevertheless, it continues being one of the most tracer pathology of the medical- surgical urgency.